E-LEARNING APPLICATIONS IN ENGLISH SUBJECTS USE THE EXAMPLE NOT EXAMPLE METHOD IN JUNIOR HIGH SCHOOLS - Erdisna -; Sri Restu Ningsih; Febriyanno Suryana; Elmi Rahmawati; Revi Gusriva (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
The problem that occurs in junior high school students is that there is no e-learning system in learning English, causing a lack of student interest in learning English material taught by the teacher because of its monotonous presentation and difficulties for students to accept. This study aims to develop an e-learning system for English lessons to help teachers and students follow the learning process and improve students' cognitive abilities. In this study, researchers used the example not example method in teaching English learning in e-learning applications. The method used in designing this website-based e-learning system uses the waterfall method with a system design tool, namely UML. The results of this study are website-based e-learning applications using the example not example method with a more creative learning appearance by adding video and audio features that can improve students' skills in both listening and speaking